Sequence and structural characteristics of the trypsin-resistant T6 surface protein of group A streptococci. - Schneewind, O (1990)
The gene for the trypsin-resistant surface T6 protein of Streptococcus pyogenes D471 (M type 6) was cloned and expressed in Escherichia coli. The complete nucleotide sequence of the gene (tee6) and its flanking regions was determined and found to include only one major open reading frame coding for a protein of 537 amino acids (Mr, 57,675). The N terminus of the deduced protein sequence exhibits features of a typical signal sequence, and the C-terminal segment was found to have a high degree of homology with the membrane anchor region of other gram-positive surface proteins, such as streptococcal M protein, wapA protein from Streptococcus mutans and staphylococcal protein A. A hexapeptide having the consensus sequence LPSTGE and located immediately upstream of the C-terminal hydrophobic segment showed the highest degree of conservation at both the protein and DNA levels, with nearly all reported surface proteins from gram-positive cocci. The amino acid composition of the T6 protein revealed 21% serine and threonine residues distributed nearly regularly throughout the molecule, and analysis of the secondary structure predicted a conformation composed of greater than 70% beta-sheet potential interrupted by beta-turns or random coils. Localization experiments in E. coli show very little T6 protein in the periplasmic space. When found here, however, this T6 protein had a molecular mass of 55 kilodaltons, similar to that extracted from the streptococci by nonionic detergent. Most of the T6 protein was found localized in the membrane fraction, where it was composed of a triple band of 60, 58, and 57 kilodaltons. The coexistence of streptococcal surface proteins which are either resistant (T protein) or sensitive (M protein) to proteolytic enzymes may offer a new dimension to the modulation of these antigens under specific biological conditions.